Research on structure optimization and motion characteristics of wearable medical robotics based on Improved Particle Swarm Optimization Algorithm - Zheng, Yi; Wang, Youqiang; Liu, Jixin (Future generation computer systems, 2022)
In order to solve the problem of movement coordination and stability between the wearable medical robotics and the wearer, analysis the structure of lower limbs and movement gait of human body, obtains the structure principle and motion characteristics of human lower limbs;Based on anthropomorphic design criteria, proposed a wearable medical robotics, use particle swarm optimization (PSO) to optimize the installation position of the hydraulic cylinder at hip joint and knee joint, The optimal parameters of the hip and knee variables were obtained through optimization. Adopt the idea of passive drive instead of active drive, designed the hydraulic drive system and control signal amplifying circuit, established the mathematical model of the four-way sliding valve with zero opening and analyzed its stability; Use AMESim software to build the model of the hydraulic system, and conducted the motion simulation test of the hydraulic system, the results show that:The working process of the hydraulic cylinder meets the characteristics of lower limbs movement of the wearer; built the experiment platform and conducted the walking attitude experiment, the result shows that:the pressure measured by the pressure sensor modules at both ends of the soles of the feet, and the mean pressure of the soles of the feet will fluctuate between 0 and 800 N with the motion of the man–machine system, the X-axis acceleration, Y-axis acceleration, Z-axis acceleration and the acceleration scalar are all changing within the range of -10 m/s2∼20 m/s2, meeting the requirements of normal human movement. •Using particle swarm optimization (PSO) to optimize the installation position of the hydraulic cylinder at hip joint and knee joint.•Due to the dynamic characteristics of hydraulic actuators affect the stability of hydraulic system in a great extent, established the mathematical model of non-symmetric hydraulic cylinder system of zero-opening four-way slide valve, through Bode diagram and Nyquist curve analyze the stability of hydraulic system; Use AMESim software to build the hydraulic system, and carry on motion simulation.•The hydraulic system reduces the structural complexity and overall quality of the wearable medical robotics driving system and provides an important reference value for the lightweight research of human–machine system.